Testosterone Effects on Biosynthesis of Coagulation Proteins - Owens, Michael R; Cimino, Catherine D; Donnelly, Joan (Thrombosis and Haemostasis, 1987)
Studies were performed to assess the effects of testosterone on synthesis of selected coagulation proteins using the isolated rat liver perfused in vitro for 10 hours, as well as effects of testosterone on plasma levels of these same proteins. Pretreatment of castrated male rat liver donors for 14 days with pellets containing placebo or testosterone, 0.5 mg, 5.0 mg or 15.0 mg had no significant effects on cumulative biosynthesis of Factor II, Factor VII, anti thrombin III, plasminogen or fibrinogen. Plasma concentrations of these proteins in liver donor animals were also unchanged by such hormonal manipulations. In contrast, biosynthesis of fibronectin was increased significantly by increasing doses of testosterone, and plasma concentrations of fibronectin in liver donor rats showed a similar effect.
Keywords: Testosterone; Liver perfusion; Coagulation proteins; Fibronectin